PELANGGARAN HAK CIPTA OLEH MALL GRAND INDONESIA YANG MENGGUNAKAN GAMBARAN TUGU SELAMAT DATANG SEBAGAI LOGO MALL - Fico Acchedya Wijaya (Jurnal Hukum Adigama, 2021)
ntellectual property rights are defined as the right to legally protect intellectual property by the laws and regulations that protect it. The importance of copyright registration is that the work created by the creator is legally protected. Anyone who uses the work of others must obtain permission from the author or copyright owner and may not copy and/or use this work for commercial purposes without the permission of the author or copyright owner. The copyright infringement process teaches businesses to pay more attention to and comply with intellectual property laws. Example from PT. Grand Indonesia was sued by the heir Henk Nuntung, the designer of the Welcome Monument at the Hotel Indonesia Roundabout. The Central Jakarta District Court ruled that Grand Indonesia Mall violated copyright law by using a sketch of the Welcome Monument as the Mall logo without permission. The research method used is the normative legal method. The results showed that PT Grand Indonesia used a sketch of the welcome monument as a PT logo. It’s normal for PT Grand Indonesia to compensate the heirs of the late Henk. With a decision on December 2, 2020, the judge agreed to some of the heirs' charges. In one of the six trials, the defendant was given a sentence of compensation for the financial losses suffered by the plaintiff in connection with the use of the Grand Indonesia Mall logo amounting to Rp1 billion, which will be paid fully as soon as the decision is made